Система відео розпізнавання жестів мови глухонімих з використанням нейронних мереж у реальному часі - Тихомиров, В. І. (ХНУРЕ, 2023)
Video system for hand sign gesture recognition using neural networks using neutral networks. Complex of methods to detect hand sings in dynamic in real time using MediaPipe and OpenCV with Python.